Case Report: Serum sickness induced by dupilumab—clinical insights and Olinkproteomic analysis - Zhu, Hongguo; Huang, Qian’e; Zheng, Linhong; Yao, Wencui; Xia, Jumei (Frontiers in Immunology, 2025)
Dupilumab is a humanized monoclonal antibody that targets interleukin-4 (IL-4) and IL-13 pathways, commonly used in the treatment of various inflammatory conditions. Despite its therapeutic efficacy, it can also lead to rare adverse reactions, including serum sickness. Studies exploring serum sickness related to dupilumab is sparse. This report presents a case involving a middle-aged woman who developed a series of symptoms after receiving dupilumab for dermatitis, which ultimately resulted in a diagnosis of serum sickness. In this case, the patient with serum sickness exhibited a range of symptoms, including fever, rash, arthralgia, and myalgia, as well as thrombotic events, transient microscopic hematuria, and abnormal signals in the spleen and kidneys. A proteomic analysis of 92 inflammatory factors in the patient’s serum was performed using Olink technology, revealing significant elevations in several cytokines, including IL-8, IL-6, Caspase-8 (CASP-8), IL-22 receptor subunit alpha-1 (IL-22 RA1), IL-5, IL-24, IL-17A, IL-20 receptor subunit alpha (IL-20RA), IL-2 receptor subunit beta (IL-2RB), and IL-10 receptor subunit alpha (IL-10RA) during the course of serum sickness. This report contributes to the existing knowledge by detailing the clinical manifestations and cytokine profile of serum sickness induced by dupilumab and suggests potential immunological mechanisms underlying this rare adverse reaction. The findings underscore the need for awareness of such reactions and provide a foundation for future research into targeted interventions.